Beginning PostgreSQL on the cloud : simplifying database as a service on cloud platforms - Shaik, Baji; Vallarapu, Avinash (Apress, 2018)
Get started with PostgreSQL on the cloud and discover the advantages, disadvantages, and limitations of the cloud services from Amazon, Rackspace, Google, and Azure. Once you have chosen your cloud service, you will focus on securing it and developing a back-up strategy for your PostgreSQL instance as part of your long-term plan. Beginning PostgreSQL on the Cloud covers other essential topics such as setting up replication and high availability; encrypting your saved cloud data; creating a connection pooler for your database; and monitoring PostgreSQL on the cloud. The book concludes by showing you how to install and configure some of the tools that will help you get started with PostgreSQL on the cloud. This book shows you how database as a service enables you to spread your data across multiple data centers, ensuring that it is always accessible. You?ll discover that this model does not expect you to install and maintain databases yourself because the database service provider does it for you. You no longer have to worry about the scalability and high availability of your database. You will: Migrate PostgreSQL to the cloud Choose the best configuration and specifications of cloud instances Set up a backup strategy that enables point-in-time recovery Use connection pooling and load balancing on cloud environments Monitor database environments on the cloud.